Students' Perceptions Of Geography Education In Middle And High Schools: The Importance Of Geography Education In The Education Curriculum, Dagana Dzongkhag, Bhutan - Pokhrel, Leela Balab; Chhetri, Ramesh Kumar (JAMBURA GEO EDUCATION JOURNAL, 2024)
A positive perception of the geography subject is crucial for students' academic success and their interest in learning. The identification of students' perceptions of subjects has been carried out in many educational curricula.  However, it is rarely studied in Bhutan. This study explores the students' performance in middle and higher secondary school and their academic performance in Dagana Dzongkhag (district). To study the students' perceptions of learning geography, the data were collected from key stages IV and V students using a convergent parallel mixed-methods design from four schools. A total of 282 students, comprising 181 from key stage IV and 101 from key stage V were selected from two middle secondary and two higher secondary schools. The quantitative data were obtained using a survey questionnaire, and the qualitative data were collected from four FGDs (focus group discussions). The findings revealed that the students have positive perceptions of learning geography, irrespective of their stages. There is a significant difference in students' perception of learning geography between key stages IV and V. The students of key stage V have a comparatively positive perception compared to those in key stage IV. It is evident from this study that students' perceptions towards the subject would also impact their academic performance. Therefore, to address the research findings, this study recommends the district education office and school management to prioritize geography education and establish proper mechanism to support it through relevant authorities. The study has also opened the way forward for future researchers to explore similar research with a larger population.